On Transitive Systems of Subspaces in a Hilbert Space - Moskaleva, Y.P.; Samoilenko, Y.S. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
Methods of *-representations in Hilbert space are applied to study of systems of n subspaces in a linear space. It is proved that the problem of description of n-transitive subspaces in a finite-dimensional linear space is *-wild for n ≥ 5.